VD_FINDINFO HC / 2015 / 133 vom 28. November 2014 - VD Tribunal cantonal (2014)
RÉPRIMANDE, SOMMATION, DILIGENCE, CONTRAT DE TRAVAIL | 59 al. 3 LPers-VD, 136 RLPers-VD, 137 RLPers-VD, 142 al. 1 RLPers-VD, 142 al. 2 RLPers-VD, 53 al. 1 CPC (CH), 53 CPC (CH), 103 CDPJ